Optimising a curriculum for clinical haematology and biochemistry in sports medicine: a Delphi approach - Fallon, K. E.; Trevitt, A. C. (British Journal of Sports Medicine, 2006)
Objectives: To investigate issues of curriculum in the context of a postgraduate sports medicine training programme, specifically in the field of clinical biochemistry and haematology.